(untitled) (Revista Brasileira de Contabilidade e Gestão, 2012)
The security of information traffic over networks of computers has become a factor of considerable concern, because with the increasing use of computers and the Internet, there was a growing number of incidents in these computing environments. Many of these incidents can cause delays of the network or even provide access to confidential information. To get an overview of what is happening on a network makes use of software packet analyzers. The packet analyzers capture and present all the data traffics flow decoding and displaying the contents of the package for detailed analysis. There are several tools packet analyzer, both free tools and proprietary tools. This paper presents a comparative study involving two proprietary tools packet analyzer and two free, in order to present the features and their advantages and disadvantages.